2022
DOI: 10.1038/s41563-022-01433-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the cellular microenvironment as probed by cells in vivo during zebrafish presomitic mesoderm differentiation

Abstract: Tissue morphogenesis, homoeostasis and repair require cells to constantly monitor their three-dimensional microenvironment and adapt their behaviours in response to local biochemical and mechanical cues. Yet the mechanical parameters of the cellular microenvironment probed by cells in vivo remain unclear. Here, we report the mechanics of the cellular microenvironment that cells probe in vivo and in situ during zebrafish presomitic mesoderm differentiation. By quantifying both endogenous cell-generated strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Many diseases are believed to be associated with cellular microenvironment mechanical properties changes. [1][2][3][4][5][6] For instance, tumor migration is influenced by mechanical parameters in the cellular microenvironment. [7][8][9][10][11][12][13][14] The extracellular matrix (ECM), as an important component of the cellular microenvironment, is a crucial factor affecting cellular activities.…”
Section: Introductionmentioning
confidence: 99%
“…Many diseases are believed to be associated with cellular microenvironment mechanical properties changes. [1][2][3][4][5][6] For instance, tumor migration is influenced by mechanical parameters in the cellular microenvironment. [7][8][9][10][11][12][13][14] The extracellular matrix (ECM), as an important component of the cellular microenvironment, is a crucial factor affecting cellular activities.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 The cellular microenvironment in situ, as found within organs or tissues, is intricately structured and plays a pivotal role in dictating the cell structure, mechanics, polarity, and function. 4,5 However, in conventional cell culture settings, such as a culture dish, cells develop randomly with undefined geometry, which poses a challenge in studying the interplay between geometric information and cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Cell geometry, with its attributes like shape and size, has a profound influence on a variety of cell functions, including but not limited to cell adhesion, proliferation, stem cell differentiation, and gene expression. The cellular microenvironment in situ , as found within organs or tissues, is intricately structured and plays a pivotal role in dictating the cell structure, mechanics, polarity, and function. , However, in conventional cell culture settings, such as a culture dish, cells develop randomly with undefined geometry, which poses a challenge in studying the interplay between geometric information and cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Autologous apoptotic cells transplantation has already found use in transplant tolerance. [11] Recent research has highlighted a growing interest in the physical characteristics of both the substrate [12][13][14] and the target, [15] which may potentially influence the engulfment process. It has been demonstrated that the mechanical characteristics of particles can influence their uptake, with the efficiency of uptake increasing in tandem with Young's modulus.…”
Section: Introductionmentioning
confidence: 99%